Child-evoked maternal negativity from 9 to 27 months: Evidence of gene–environment correlation and its moderation by marital distress. (12th September 2014) - Fearon, R. M. Pasco; Reiss, David; Leve, Leslie D.; Shaw, Daniel S.; Scaramella, Laura V.; Ganiban, Jody M.; Neiderhiser, Jenae M.
Abstract: Past research has documented pervasive genetic influences on emotional and behavioral disturbance across the life span and on liability to adult psychiatric disorder. Increasingly, interest is turning to mechanisms of gene–environment interplay in attempting to understand the earliest manifestations of genetic risk. We report findings from a prospective adoption study, which aimed to test the role of evocative gene – environment correlation in early development. Included in the study were 561 infants adopted at birth and studied between 9 and 27 months, along with their adoptive parents and birth mothers. Birth mother psychiatric diagnoses and symptoms scales were used as indicators of genetic influence, and multiple self-report measures were used to index adoptive mother parental negativity. We hypothesized that birth mother psychopathology would be associated with greater adoptive parent negativity and that such evocative effects would be amplified under conditions of high adoptive family adversity. The findings suggested that genetic factors associated with birth mother externalizing psychopathology may evoke negative reactions in adoptive mothers in the first year of life, but only when the adoptive family environment is characterized by marital problems. Maternal negativity mediated the effects of genetic risk on child adjustment at 27 months. The results underscore the importance of genetically influenced evocative processes in early development.